The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s12602-010-9051-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Non-Nutritional Factors for a Cost-Effective Enhancement of Nisin Production Using Orthogonal Array Method

Abstract: In order to increase nisin production in a cost-effective manner, non-nutritional factors as well as nutritional parameters must be optimized. In this study, optimization of the most important non-nutritional factors for nisin production using orthogonal array method was performed. Optimization of temperature, agitation, age and size of inoculum, medium initial pH value and flask volume/medium volume ratio in de Man, Rogosa and Sharpe (MRS) medium in batch fermentation was accomplished. Nisin was produced by L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Recently, nisin has been shown to have potential clinical use in the treatment of various diseases, such as cancer, oral diseases, and immunological disorders (Shin et al, 2016;Małaczewska et al, 2019;Qu et al, 2019). Based on this wide range of potential applications, many approaches have been attempted to improve the nisin yield, such as optimization of fermentation conditions, traditional random mutagenesis and selection, genome shuffling, and more (Wu et al, 2009;Tafreshi et al, 2010;Zhang et al, 2014). The growth of L. lactis, a major producer of nisin, is usually inhibited by the high concentration of lactic acid secreted during fermentation (Zhang et al, 2014), which has become the greatest challenge to the biotechnological engineering of this strain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nisin has been shown to have potential clinical use in the treatment of various diseases, such as cancer, oral diseases, and immunological disorders (Shin et al, 2016;Małaczewska et al, 2019;Qu et al, 2019). Based on this wide range of potential applications, many approaches have been attempted to improve the nisin yield, such as optimization of fermentation conditions, traditional random mutagenesis and selection, genome shuffling, and more (Wu et al, 2009;Tafreshi et al, 2010;Zhang et al, 2014). The growth of L. lactis, a major producer of nisin, is usually inhibited by the high concentration of lactic acid secreted during fermentation (Zhang et al, 2014), which has become the greatest challenge to the biotechnological engineering of this strain.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, poor production is often a bottleneck in large-scaled production of bacteriocins. Previous studies have shown that bacteriocin production can be increased by optimization of growth conditions such as cultivation temperature, pH, aeration and growth medium (Biswas et al, 1991; Parente and Ricciardi, 1994; Aasen et al, 2000; Cabo et al, 2001; Nel et al, 2001; Guerra and Pastrana, 2002; Penna and Moraes, 2002; Tafreshi et al, 2010). In addition, various heterologous expression systems have been reported for increased bacteriocin production (Horn et al, 2004; Kong and Lu, 2014; Jimenez et al, 2015; Jiang et al, 2016; Mesa-Pereira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%